2020
DOI: 10.5334/aogh.2650
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Status and Associated Factors among Street Children 9–24 Months Old in Sidama Region, Ethiopia

Abstract: Background: Childhood non-vaccination can have different short-and long-term negative outcomes on their health. In Ethiopia, in addition to low coverage of full vaccination, street children were among the neglected part of the community who were missed during planning and reporting vaccination coverage. Moreover, there is no related research conducted on this title specifically. Objective: The objective of the study was to assess the vaccination status and its associated factors among street children 9-24 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…Children, whose health cards were presented, whose mothers wanted the pregnancy then, live in households that are Catholics, Muslims, Traditionalists, Ekoi, Fulani, Hausa, Ibibio, Igala, Igbo, Ijaw, Kanuri, Tiv, and Yoruba and reside in North East and North West zones have lower odd of being under-vaccinated. This is similar to results obtained by Deressa et al (2020), Yenit et al (2015), Favin et al (2012), and Boulton et al (2018). Generally, most of the under-vaccinated children were delivered at home, did not receive PNC, their mothers had low literacy level and they live in poorer households.…”
Section: Discussionsupporting
confidence: 87%
“…Children, whose health cards were presented, whose mothers wanted the pregnancy then, live in households that are Catholics, Muslims, Traditionalists, Ekoi, Fulani, Hausa, Ibibio, Igala, Igbo, Ijaw, Kanuri, Tiv, and Yoruba and reside in North East and North West zones have lower odd of being under-vaccinated. This is similar to results obtained by Deressa et al (2020), Yenit et al (2015), Favin et al (2012), and Boulton et al (2018). Generally, most of the under-vaccinated children were delivered at home, did not receive PNC, their mothers had low literacy level and they live in poorer households.…”
Section: Discussionsupporting
confidence: 87%
“…The smallest (n = 107) and largest (n = 2941) sample sizes were reported in studies conducted in the Southern Nations, Nationalities, and People’s Region (SNNPR) and nationwide survey. 21 , 39 The details of the included studies’ characteristics and descriptions are presented using a table ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 52 studies underwent a critical appraisal, and 14 studies were excluded from the synthesis due to the relatively poor methodological quality, data inconsistency, and unavailability or incompleteness of the data. The remaining 38 studies 17,21,22,24,26,27,3364 were included in this systematic review and meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The result was in line with previous reports. 13 , 59 , 60 Maternal and child health care are interrelated. The more women adhere to maternal and child care, the more women know benefit, understand the appointment and improved communication with care providers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the opposite. 13,57,59,60,[63][64][65] Institutional deliveries advantage for further maternal and childcare is not questionable. However, the inability of caregivers to transition from delivery services and to later continue with care provided for their children is a major concern in sub-Saharan Africa.…”
mentioning
confidence: 99%